Molecular cloning characterization and expression analysis of CpCBF2 gene in harvested papaya fruit under temperature stresses - Zhu, Xiaoyang; Li, Xue ping; Chen, Weixin; Lu, Wangjin; Mao, Jia; Liu, Tongxin (Electronic Journal of Biotechnology, 2013)
Background: C-repeat binding factors (CBFs) are transcription factors that regulate the expression of a number of genes related to abiotic stresses. Few CBF genes have been cloned from other plants but no report in papaya. In present study, a full-length cDNA, designated as CpCBF2, was cloned from papaya using in silico cloning and 5’- rapid amplification cDNA ends (RACE). Sequence analysis was performed to understand the gene function. The expression pattern of CpCBF2 in papaya under low (7°C) and high temperature (35°C) stresses was examined using real-time quantitative polymerase chain reaction (RT-qPCR). Results: The full-length cDNA of CpCBF2 was 986-bp, with a 762-bp open reading frame (ORF) encoding a 254 amino acid polypeptide. CpCBF2 contained several major highly conserved regions including the CBF-family signature PKRRAGRKKFQETRHP and FADSAW in its amino acid sequence. Phylogenetic tree and three-dimensional structure analysis showed that CpCBF2 had a relatively close relationship with other plant CBFs. Gene expression analysis showed that high temperature stress had little effect on the expression of CpCBF2 but low temperature repressed CpCBF2 expression. Conclusion: The results showed that CpCBF2 may involve in different roles in temperature stress tolerance. This study provided a candidate gene potentially useful for fruit temperature stress tolerance, although its function still needs further confirmation.